GENDER POLICY OF UZBEKISTAN: ISSUES OF WOMEN’S PARTICIPATION IN STATE AND COMMUNITY MANAGEMENT - Балтабаева М.М (TARIXIY TADQIQOTLAR, 2024)
The article covers issues of gender policy aimed at ensuring women’s participation in state and community management in Uzbekistan. In particular, international documents, legislative documents of the Republic of Uzbekistan, archival funds and non-governmental organizations that protect women’s interests include the issues of ensuring gender equality and expanding the rights and opportunities of all women in the sustainable development goals of the UN and the national goals of Uzbekistan in the field of sustainable development until 2030. analyzed based on information from current archives.